2022
DOI: 10.1186/s12917-022-03384-4
|View full text |Cite
|
Sign up to set email alerts
|

Low transmission rates of Equine infectious anemia virus (EIAV) in foals born to seropositive feral mares inhabiting the Amazon delta region despite climatic conditions supporting high insect vector populations

Abstract: Background Marajó Island, within in the Amazon River Delta, supports numerous bands of feral equids including the genetically distinct Marajoara horses. Approximately 40% of the equids on the island are infected with Equine infectious anemia virus (EIAV). This high seropositivity rate coupled with the need to preserve rare breeds such as the Marajoara horse precludes euthanasia as the primary means for controlling EIAV in this region. In the absence of iatrogenic transmission, spread of this le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The association between increased precipitation and EIAV may be due to the formation and maintenance of water bodies and favourable conditions for vector breeding sites and enhanced environmental suitability (Hemming-Schroeder et al, 2018). This is especially true for regions where EIAV is endemic, and hot, humid rainforest environments support a very high density of horse and deer fly populations throughout the year (Resende et al, 2021). On the other hand, we also found that municipalities with high in-degree are more likely to have farms that tested positive for EIAV, as expected since the most relevant mode of between-farm transmission has been related to the transportation of infectious animals between farms (Firestone et al, 2011(Firestone et al, , 2012Spence et al, 2017;Squarzoni-Diaw et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The association between increased precipitation and EIAV may be due to the formation and maintenance of water bodies and favourable conditions for vector breeding sites and enhanced environmental suitability (Hemming-Schroeder et al, 2018). This is especially true for regions where EIAV is endemic, and hot, humid rainforest environments support a very high density of horse and deer fly populations throughout the year (Resende et al, 2021). On the other hand, we also found that municipalities with high in-degree are more likely to have farms that tested positive for EIAV, as expected since the most relevant mode of between-farm transmission has been related to the transportation of infectious animals between farms (Firestone et al, 2011(Firestone et al, , 2012Spence et al, 2017;Squarzoni-Diaw et al, 2021).…”
Section: Discussionmentioning
confidence: 99%